Educational Media Perspectives of the Qur'an and Hadith: Its Development in the Digital Era - Muhammad Sufyan As-Tsauri; Hafid Hafid; Ilham Faisal Abduh (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2022)
Education is a basic need for society to achieve progress. In the educational process, learning activities occur, which in this case, require media. The purpose of this study is to discuss the verses of the Qur'an and Hadith regarding Islamic Educational Media. The method in this study uses a literature review. The results of this study explain that in the early days of Islamic education, the Prophet used this educational medium in conveying Islamic teachings to his friends, using the media of the Prophet's behavior, parts of the body, pictures, heaven, and earth, sun and moon, and silk. Along with the times, this educational media was then developed through diagrams, graphs, globes, videos, tapes, power points, and others. From the results of these studies, teachers should continue to innovate educational media using themselves and the natural environment to respond to changing times in the digital era. There are four principles of using media: choosing the right type of media, taking into account the maturity level of students, presenting the media appropriately, and placing the media in the right time, place, and situation.Pendidikan merupakan kebutuhan pokok bagi masyarakat untuk mencapai kemajuan. Dalam proses pendidikan terjadi kegiatan pembelajaran yang dalam hal ini membutuhkan media. Tujuan dari penelitian ini untuk membahas ayat-ayat Al-Qur’an dan hadis berkenaan dengan Media Pendidikan Islam. Metode dalam penelitian ini menggunakan kajian studi pustaka. Hasil penelitian ini menjelaskan bahwa pada masa awal pendidikan Islam, Rasulullah telah mengaplikasikan media pendidikan ini dalam menyampaikan ajaran Islam kepada para sahabat, dengan menggunakan media perilaku Rasulullah sendiri, anggota badan, gambar, langit dan bumi, matahari dan bulan, dan sutra. Seiring dengan perkembangan zaman, media pendidikan ini kemudian dikembangkan berupa diagram, grafik, globe, video, kaset, power point dan lain-lain. Dari hasil penelitian tersebut, maka guru hendaknya terus melakukan inovasi media pendidikan baik menggunakan dirinya sendiri maupun alam sekitar untuk menjawab perubahan zaman di era digital. Terdapat empat prinsip penggunaan media yaitu memilih jenis media dengan tepat, memperhitungkan tingkat kematangan siswa, menyajikan media dngan tepat, dan menempatkan media di waktu, tempat, dan situasi yang tepat.